Mobile phone use, productivity and labour market in Tanzania - Aimable Nsabimana; Patricia Funjika (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Access to mobile phone has increased substantially over the last decade in sub-Saharan Africa. The evidence suggests that increased use of mobile phones in the region has upgraded the market prices received by producers for their cash crops, but so far there is limited knowledge on labour market transitions effects of mobile phone access. In this study, we use farm household and individual labour force information, from LSMS-ISA Tanzania National Panel Survey, to examine the impact of mobile phone ownership on labour markets and farm productivity in the country. The study shows that successive increases in mobile phone use lead to movement of labour share from agriculture into non-farming sectors. The results also show that mobile phone access significantly reduces the intensity of work by household members on the farm and is instead associated with an increase in hired farm workers. Our results also show that mobile phone access has heterogeneous labour market effects, depending on the age of individuals. Given the important surge of in formation communication technology in sub-Saharan Africa, including Tanzania, the results suggest that using mobile phones to stimulate agricultural developments would improve marginal productivity of labour in the farming sector and induce a surge in off-farm employment opportunities.
Keywords: Q12; O1; O33; 330; mobile phone; farm productivity; market prices; Tanzania